Democracy and modernisation in the making of the South African trade union movement: the dilemma of leadership, 1973 - 2000 - Buhlungu, Maxwell Sakhela (My University, 2001)
Through an examination of the tradition of 'worker control' and the changing role of full-time officials in the post-1973 unions, this thesis examines a theme which has preoccupied the minds of sociologists since the pioneering work of Sidney and Beatrice Webb at the turn of the twentieth century, namely, the contradictory relationship between the imperatives of democracy and administrative efficiency in trade union organisation. The post-1973 unions affiliated to the Congress of South African Trade Unions (COSA TU) epitomise the worker control tradition, hence the choice of this federation and its affiliates to illustrate this contradiction. The findings of this thesis show that membership growth coupled with the attainment of economic and political citizenship by black workers in an era characterised by the insertion of South Africa into a changing global political economy has eroded the tradition of worker control. Accompanying these changes is organisational modernisation, that is, processes of change and reconsMution in an organisation which result from a quest to achieve its goals and ensure its durability and adaptability to changing internal and external circumstances. One of the implications of organisational modernisation is that union officials now play a more active and influential role in union decision-making, thus intensifying the tension between the imperatives of democracy on the one hand and administrative efficiency on the other. However, the findings also suggest that these tensions are subject to a contestation which takes the form of different approaches to organisational modernisation or what we call modernisation projects. An examination of the changing role of full-time union officials shows that the 'activist organiser' of the era of the liberation struggle has been transformed into three types - the ideological unionist, the 'entrepreneur' and the career unionist - all of whom pursue different and competing modernisation projects. The thesis argues that organisational modernisation intensifies these contradictions, leading to the dilemma of leadership, rather than the 'iron law of oligarchy' as propounded Robert Michels. This dilemma highlights a tension between two competing imperatives in a trade union, namely, the need to be democratic on the one hand, and the desire to achieve administrative efficiency on the other. The thesis suggests that the iron law of oligarchy is not the sole and final trajectory of an organisation such as a trade union. Instead we propose a novel resolution of the classic democracy/oligarchy dichotomy, namely, the maintenance and intensification of the dilemma of leadership. This approach denotes a state of affairs where the union is in transition but the final outcome is indeterminate because of contestation and the ever-changing balance of power. It implies that democracy and administrative efficiency are equally important imperatives in an organisation, imperatives which should be seen as complementary rather than contradictory.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy (Sociology) to the Faculty of Humanities, Social Sciences and Education, University of the Witwatersrand, Johannesburg, 2001